A INFLUÊNCIA MORFOESTRUTURAL DA REDE DE DRENAGEM NA BACIA DO ALTO CURSO DO RIO PITANGUI - PARANÁ - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
Methods of morphostructural analysis, based on morphometric indices constitute important tools to assess the behavior of hydrographic systems. They are cheap and quick methods of collecting information, passable to correlate with field data. Backed up on this assertive, the aims of the research was to characterize the main morphostructural in behavior of drainage network in hydrographic basin of Alto Pitangui, Paraná. The Pitangui River tributary the of Tibagi, classified as antecedent river, transits among the igneous and metamorphic rock belonging to Cunhaporanga Granitic Complex and Itaiacoca Group, the Paranaense First Plateau, in its upper course, and Paleozoic rocks of the eastern edge of the Paraná Basin, in the Secound Plateau, the middle and lower course. The morphometry has relied on data extraction about Stream-length index (SL index), Asymmetric Factor (AF) and Drainage Basin Symmetry (DBS), longitudinal profile and transverse profile the basin. The study area has a strong structural and tectonic control which directly influences in elongated shape, NE-SW direction, of the hydrographic basin, with the main channel sometimes notched and embedded into strutural lineaments, or an extensive flood plain in assymmetric valleys and presence of terraces and oxbow lakes. Its main characteristic is represented by longitudunal misfit. The gradient index made possible the detection of 6 snippets with anomalous gradients distribued along its course. Are anomalies of second order, associated to lithological changes, or relief lineaments and channel confluences. The varation in the main channel behavior and some of its tributaries has a direct relation to the fact circular by a morphostrutural transition region, with strong influences of Ponta Grossa Arch and the Devonian Escarpment presence. The Upper course Pitangui River reflects scathing manner the importance of tectonic events and geological context to with is inserted, presenting diverse anomalies, which are indicate imbalances located along some drainages.
A INFLUÊNCIA MORFOESTRUTURAL DA REDE DE DRENAGEM NA BACIA DO ALTO CURSO DO RIO PITANGUI - PARANÁ
Keywords: geomorfologia; morfoestrutura; rede hidrográfica; anomalias de drenagem; Bacia hidrográfica do Alto Pitangui.; geomorphology; morphostructure; hydrographic network; anomalies drainage; Basin of Alto Pitangui; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA